2016
DOI: 10.1002/2016jd025381
|View full text |Cite
|
Sign up to set email alerts
|

How dual‐polarization radar observations can be used to verify model representation of secondary ice

Abstract: In this paper it is discussed how dual‐polarization radar observations can be used to verify model representations of secondary ice production. An event where enhanced specific differential phase, Kdp, signatures in snow occur at the altitudes where temperatures lie in the range between −8 and −3°C is investigated. By combining radar and surface‐based precipitation observations it is shown that these dual‐polarization radar signatures are most likely caused by ice with concentrations exceeding those expected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 50 publications
2
40
0
Order By: Relevance
“…The signature of needle and/or columnar crystals in a temperature range from À8 to À3°C, where ice particles seeded in the MPL and secondary ice formation via the Hallett-Mossop ice multiplication mechanism (Hallett & Mossop, 1974) could be active, is often observed in Arctic mixed-phase clouds in linear depolarization ratio measurements . Similar signatures were observed in midlatitude winter storms and convective systems (e.g., Giangrande, Toto, Bansemer, et al, 2016;Kumjian et al, 2016;Kumjian & Lombardo, 2017;Sinclair et al, 2016;Zawadzki et al, 2001). Kumjian et al (2016) observed K DP enhancements produced by needle and columnar crystals in secondary ice formation regions.…”
Section: Mixed-phase Layersupporting
confidence: 66%
See 1 more Smart Citation
“…The signature of needle and/or columnar crystals in a temperature range from À8 to À3°C, where ice particles seeded in the MPL and secondary ice formation via the Hallett-Mossop ice multiplication mechanism (Hallett & Mossop, 1974) could be active, is often observed in Arctic mixed-phase clouds in linear depolarization ratio measurements . Similar signatures were observed in midlatitude winter storms and convective systems (e.g., Giangrande, Toto, Bansemer, et al, 2016;Kumjian et al, 2016;Kumjian & Lombardo, 2017;Sinclair et al, 2016;Zawadzki et al, 2001). Kumjian et al (2016) observed K DP enhancements produced by needle and columnar crystals in secondary ice formation regions.…”
Section: Mixed-phase Layersupporting
confidence: 66%
“…Schrom et al (2015) suggested a polarimetric technique to separate contributions from aggregates and dendrites in the DGL of midlatitude winter storms. Polarimetric signatures of the secondary ice mixed with aggregated and rimed snow in layers with temperature around À5°C were found by cloud and precipitation radar measurements in high-latitude deeper snow clouds Sinclair et al, 2016), midlatitude mesoscale convective systems Kumjian et al, 2016), and midlatitude snowstorms (Kumjian & Lombardo, 2017). However, combining polarimetric measurements with the analysis of Doppler spectra yields a much better chance to identify and separate different types of ice, and to quantify their amounts if their corresponding fall velocities are associated with separate peaks in the Doppler spectrum.…”
Section: Introductionmentioning
confidence: 96%
“…Sinclair et al (2016) found a similar result when modeling a frontal cloud over Finland with WRF, where model results compared best with radar-derived N ice with similar H-M changes. Sinclair et al (2016) found a similar result when modeling a frontal cloud over Finland with WRF, where model results compared best with radar-derived N ice with similar H-M changes.…”
Section: Modeling Sipsupporting
confidence: 56%
“…By identifying particle types in observations, we may conclude what processes took place. Currently, dual-polarization radar observations are used in fuzzy logic classification to identify the dominant hydrometeor type present in a radar volume (e.g., Chandrasekar et al, 2013;Thompson et al, 2014). Such methods work very well for classification of hydrometeors of summer precipitations and some features of winter precipitation types.…”
Section: Introductionmentioning
confidence: 99%